Degradation of a series of fluorinated acrylates and methacrylates initiated by OH radicals at different temperatures. Issue 8 (27th January 2020) - García, P. Lugo; Rivela, C. B.; Gibilisco, R. G.; Salgado, S.; Wiesen, P.; Teruel, M. A.; Blanco, M. B.
Abstract : Rate coefficients for the gas-phase reactions of OH radicals with a series of fluorinated acrylates and methacrylates have been measured for the first time as a function of temperature in the range 290–308 K. Abstract : Rate coefficients for the gas-phase reactions of OH radicals with a series of fluorinated acrylates and methacrylates: 2, 2, 2-trifluoroethylmethacrylate ( k 1 ), 1, 1, 1, 3, 3, 3-hexafluoroisopropylacrylate ( k 2 ), 1, 1, 1, 3, 3, 3-hexafluoroisopropylmethacrylate ( k 3 ), and 2, 2, 2-trifluoroethylacrylate ( k 4 ) have been measured for the first time as a function of temperature in the range 290–308 K. The kinetic data obtained were used to derive the following Arrhenius expressions (in units of cm 3 per molecule per s): k 1 = (2.13 ± 0.68) × 10 −18  exp[(4745 ± 206)/ T ], k 2 = (8.72 ± 0.68) × 10 −15  exp[(2166 ± 205)/ T ], k 3 = (6.30 ± 0.51) × 10 −17  exp[(3721 ± 153)/ T ] and k 4 = (3.93 ± 0.43) × 10 −16  exp[(3140 ± 129)/ T ]. The experiments were performed at normal atmospheric pressure in synthetic air using a 1080 L photoreactor and coupled with FTIR analysis to monitor the decay of the substances of interest and the reference compounds. The obtained negative temperature dependencies are in agreement with a mechanism implying an initial addition of the OH radical to the double bond. Atmospheric implications are discussed with reference to the rate coefficients obtained as a function of the temperature.